Surface area measurement using rendered three-dimensional ultrasound imaging: an in-vitro phantom study. - Ioannou, C; Sarris, I; Yaqub, M; Noble, J; Javaid, M; Papageorghiou, A (2011)
OBJECTIVE: Cranial sutures and fontanelles can be reliably demonstrated using three-dimensional (3D) ultrasound with rendering. Our objective was to assess the repeatability and validity of fontanelle surface area measurement on rendered 3D images. METHODS: This was an in-vitro phantom validation study. Four holes, representing fontanelles, were cut on a flat vinyl tile. The phantom was scanned in a test-tank by two sonographers, at four different depths and using two different 3D sweep directions. The surface areas were measured on scan images and also directly from the phantom for comparison. Coefficients of variation (CVs), intraclass correlation coefficients (ICCs) and Bland-Altman plots were used for repeatability analysis. Validity was expressed as the percentage difference of the measured area from the true surface area. RESULTS: Validity of measurement was satisfactory with a mean percentage difference of - 5.9% (median = - 3.5%). The 95% limits of agreement were - 23.9 to 12.1%, suggesting that random error is introduced during image generation and measurement. Repeatability of caliper placement on the same image was higher (intraobserver CV = 1.6%, ICC = 0.999) than for measurement of a newly generated scan image (intraobserver CV = 5.5%, ICC = 0.992). Reduced accuracy was noted for the smallest shape tested. CONCLUSION: Surface area measurements on rendered 3D ultrasound images are accurate and reproducible in vitro.